Identifying the preferable rheumatoid arthritis subgroups for intervention with the anti-RANKL antibody denosumab to reduce progression of joint destruction. Issue 2 (30th July 2020) - Tanaka, Yoshiya; Soen, Satoshi; Ishiguro, Naoki; Yamanaka, Hisashi; Yoneda, Toshiyuki; Tanaka, Sakae; Ohira, Takeshi; Nitta, Takaya; Okubo, Naoki; Genant, Harry; van der Heijde, Desirée; Takeuchi, Tsutomu
Abstract : Objectives: To clarify which rheumatoid arthritis (RA) patients benefit most from the anti-receptor activator of nuclear factor-κB ligand antibody denosumab to reduce the progression of joint destruction. Methods: We pooled patient data from the 12-month, double-blind, placebo-controlled DRIVE (phase II) and DESIRABLE (phase III) studies. In DRIVE, concomitant treatment was limited to methotrexate, salazosulfapyridine and bucillamine. In DESIRABLE, patients could receive any disease-modifying antirheumatic drug. RA patients were randomised to denosumab 60 mg every 6 months (Q6M), every 3 months (Q3M) or placebo. Efficacy was assessed by van der Heijde-modified total Sharp score (mTSS), bone erosion score (ES) and joint space narrowing score (JSNS). Change in mTSS was assessed in subgroups stratified by risk factors for radiographic damage if the interaction factor was significant. Results: The pooled analysis included 909 patients. Denosumab reduced worsening of mTSS (mean (SD)) at 12 months in the Q6M (0.88 (3.30), p=0.0024) and Q3M (0.66 (2.16), p=0.0002) groups versus placebo (1.50 (3.73)). This reduction in mTSS progression was due to the change in ES (Q6M, 0.44 (1.89), p=0.0006; Q3M, 0.20 (0.86), p<0.0001) versus placebo (0.98 (2.54)); no effect was observed on JSNS. Anti-cyclic citrullinated peptide (CCP) antibodies, glucocorticoid use and baseline ES showed a significant interaction. Denosumab was particularly effective in patients who were anti-CCP antibody positive (p<0.05). Changes in mTSS versus placebo were observed in all denosumab dose groups, regardless of glucocorticoid use and baseline ES. Conclusions: Denosumab broadly reduced the progression of joint destruction in RA patients with risk factors for radiographic damage such as especially anti-CCP antibody positivity.